Relations Between Posttraumatic Stress Disorder Symptoms and Positive Memory Characteristics Among Women Reporting Intimate Partner Violence: A Micro-Longitudinal Study - Contractor, Ateka A. (Journal of interpersonal violence, 2023)
Evidence links posttraumatic stress disorder (PTSD) symptoms to positive autobiographical memory characteristics. To extend this research, we uniquely utilized micro-longitudinal data to examine (1) the trajectory of PTSD symptom count across 30 days; and (2) if more vividness and accessibility of retrieved positive memories at the daily level predicted decreases in the trajectory of PTSD symptom count across 30 days. The current study was a secondary data analysis of a larger study. The sample included 74 women who reported physical or sexual victimization in the past 30 days by their current male partner and reported the use of alcohol and/or drugs during that time (Mage = 39.68 years; 37.80% with diagnostic PTSD; 43.2% White; 37.8% Black or African American). They completed thrice daily measures of PTSD symptoms and positive memory characteristics (vividness and accessibility) across 30 days. Results of the random effects longitudinal multilevel model indicated that, on average, the relation between PTSD symptom count and positive memory vividness was positive and statistically significant (0.19, 95% Confidence Interval [CI] [0.2, 0.35]); and the relation between PTSD symptom count and positive memory accessibility was positive and statistically significant (0.31, 95% CI [0.15, 0.47]). The relationship between PTSD symptom count and positive memory vividness/accessibility (i.e., slopes) varied significantly across participants, with a wide range of positive and negative regression coefficients. Future research needs to investigate why and how positive memory vividness and accessibility may relate to trajectories of PTSD symptoms over time, with potential clinical implications for positive memory interventions addressing PTSD.